PERANCANGAN BUKU FOTOGRAFI KULINER TRADISIONAL PROVINSI JAWA TIMUR - Nathania Handoko; Aditya Nirwana; Didit Prasetyo Nugroho (Fakultas Sains Dan Teknologi Universitas Ma Chung, 2022)
Indonesia has a culture that is not just customs, regional, clothes, regional dances, regional songs, language and scripts, but Indonesian also has cuisine that is as diverse as the existing culture. Culinary or special food from an area is also included in a culture that has been inherited by our ancestors for the Indonesia people. Culinary from East Java itself is a culinary that needs to be maintained and preserved by the younger generation who will come with the aim that a nation and culture in East Java is not displaced by the culinary arts that have just entered Indonesian culture. This East Java Culinary guide book is specially designed to inform future generation of young people, that East Java Culinary is broad and has the hope of participating in preserving and introduction East Javanese Culinary.